2020
DOI: 10.1136/rmdopen-2020-001206
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of extra-articular manifestations in axial spondyloarthritis and their influence on TNF-inhibitor prescribing patterns: results from the British Society for Rheumatology Biologics Register in Ankylosing Spondylitis

Abstract: ObjectivesExtra-articular manifestations (EAMs) are important systemic features of axial spondyloarthritis (axSpA), which may influence the choice of tumour necrosis factor-inhibitor (TNFi). We examined the cumulative incidence and predictors of EAMs and the influence of these on first TNFi choice in a ‘real-world’ cohort of patients with axSpA.MethodsClinical and patient-reported outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
5
8
0
Order By: Relevance
“…The correlation between decreased ALB levels and increased risk of incident IBD was stronger in participants of younger age, and this finding could be related to the accumulation of the metabolic risk factors with aging [45]. Consistently, a previous study indicated an inverse association between TP (composed of ALB and globulin) and risk, which was probably attributable to ALB [46].…”
Section: Discussionsupporting
confidence: 81%
“…The correlation between decreased ALB levels and increased risk of incident IBD was stronger in participants of younger age, and this finding could be related to the accumulation of the metabolic risk factors with aging [45]. Consistently, a previous study indicated an inverse association between TP (composed of ALB and globulin) and risk, which was probably attributable to ALB [46].…”
Section: Discussionsupporting
confidence: 81%
“…We found patients with AU to be more often male and HLA-B27 positive, thus, in this sense our data are in agreement with results previously reported suggesting AU to occur more commonly among male patients [24][25][26] and its presence to be related to HLA-B27. 20,27,28 We also observed an association between current/ recent AU and lower disease activity assessed by BASDAI. This intriguing association might be indicative of a disconnection between ocular and musculoskeletal inflammation.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we demonstrated that history of PSO was associated with a BASDAI increase of 0.31 points and a BASFI increase of 0.37 points. Associations between PSO and increased diagnostic delay, 17 indicating a need for specific referral strategies on the level of dermatologists, and between absence of HLA-B27 and higher frequency of PSO 18 20 had been reported previously. Moreover, an association between diagnostic delay and worse outcomes in axSpA 21 and significantly higher BASDAI and BASFI scores in HLA-B27-negative patients with axSpA 18 , 19 had been described.…”
Section: Discussionsupporting
confidence: 62%
“…The prevalence of IBD in the British Society for Rheumatology Biologics Register (BSRBR-AS), which comprises two cohorts of axSpA patients starting their first biologic therapy and those naïve to such therapy, has been reported as 10.2% (3). The same report found that being HLA-B27 negative was the only clinical factor associated with the diagnosis of IBD.…”
Section: Introductionmentioning
confidence: 99%